HBA1C AS AN INDIRECT MARKER OF HYPERTRIGLYCERIDEMIA IN TYPE 2 DIABETES MELLITUS - Zaidi, Syed Muhammad Hammad; Ghafoor, Abdul; Randhawa, Fawad Ahmed (Journal of Ayub Medical College Abbottabad, 2015)
Background: Diabetes is usually accompanied by dyslipidaemia, and among these triglyceride levels are related to the insulin resistance in type 2 diabetes. HbA1c which is an indicator of diabetes control can depict the severity of hypertriglyceridemia. The objective of this study was to determine the correlation between HbA1c and Triglyceride levels in type 2 Diabetes mellitus. Methods: A sample of 150 diabetic patients fulfilling the inclusion and exclusion criteria were selected for this cross-sectional study .Patient included were type 2 Diabetes Mellitus with HbA1c ‰¥7. Patients with history of cardiovascular disease, taking lipid lowering medications, smoker and history of cerebral stroke were excluded. HbA1c and triglyceride levels were noted .Study patients were further stratified on the basis of severity of HbA1c and Triglyceride values. The correlation between HbA1c and Triglyceride levels were established with Pearson Correlation. Results: Among total number of 150 patients 44% (n=70) were male and 50.3% (n=80) were female. The correlation of HbA1c with Triglyceride as estimated by Pearson Correlation was positive (p=0.033, r=0.033) and statistically significant. Conclusions: In type 2 diabetes mellitus there is a predictable relationship between Triglycerides and HbA1c